Integration of the Steam Approach and Micro-Research in Teaching Biology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the integration of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach with the micro-research method in the teaching of biology. The combination of these two innovative educational strategies aims to enhance students’ critical thinking, creativity, and problem-solving skills through active, research-based learning. The study emphasizes the importance of transforming biology lessons from traditional theoretical instruction into practical, exploratory experiences that mirror real scientific investigations. Within the framework of the STEAM approach, micro-research provides opportunities for students to apply interdisciplinary knowledge and technological tools to biological problems, thus encouraging inquiry-based learning. By conducting small-scale experiments, observations, and analytical tasks, students develop a deeper understanding of biological concepts and their interconnection with technology and the environment. The article also examines the pedagogical, psychological, and methodological aspects of implementing micro-research, highlighting its role in shaping scientific curiosity, self-directed learning, and environmental awareness among students. Furthermore, the integration of micro-research into STEAM-based lessons supports personalized education, enabling learners to discover their interests, test hypotheses, and draw conclusions from empirical data. The paper discusses best practices for lesson design, assessment criteria, and teacher facilitation techniques to ensure effective classroom application. Overall, the study concludes that incorporating micro-research within the STEAM framework not only enriches biology education but also contributes to the holistic development of learners, preparing them for future scientific and ecological challenges.